Perancangan Laporan Keuangan Berbasis Microsoft Excel Sesuai Sak Emkm Pada Umkm Suka Laundry - Carissa Sukma, Diyah One; Dewianawati, Dwi; Perdana, Buyung Cahya (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
Suka Laundry is a micro, small, and medium enterprise (MSME) in the home industry engaged in laundry and ironing services since 2019. This research aims to create a financial report system that is easy to operate with Microsoft Excel and can prepare financial reports according to SAK EMKM at MSMEs Suka Laundry in Mojosari. This research is descriptive qualitative research, while the data collection method in this study uses interview, observation, and literature study techniques according to the research topic. The results of this study are an accounting information system that can support the process of recording financial statements. With this Microsoft Excel-based accounting information system, it is hoped that it can help Suka Laundry SMEs in managing the financial statements in the SMEs